Primary neuroendocrine carcinoma of the fallopian tube with exceeding 10 years follow-up: Case report and review of the literature - Jun Ma; Yujing Tang; Wei He; Jun Shi (Gynecologic Oncology Reports)
Neuroendocrine carcinomas typically originate from the digestive system and lungs; however, their occurrence in the female genital tract, particularly in the fallopian tube, is exceedingly rare. Currently, there is no established treatment guideline for neuroendocrine neoplasms of the fallopian tube. In this report, we presented a case of small cell neuroendocrine carcinoma of the fallopian tube, with a survival period exceeding 10 years—which is the longest recorded survival among reported cases of fallopian tube neuroendocrine tumors. The patient underwent a standard open radical tumor resection and lymphadenectomy, followed by adjuvant chemotherapy with cisplatin and etoposide, offering valuable evidence for potential standardized treatment approaches in such rare case.